Life cycle assessment of the building industry: An overview of two decades of research (1995-2018) - Bahramian, Majid; Yetilmezsoy, Kaan (ELSEVIER SCIENCE SA, 2020)
An overview of current status of the available literature on Life Cycle Energy, Life Cycle Greenhouse gasses, and Conventional Life Cycle Assessment of commercial and residential buildings was presented with respect to their height. A narrative literature review was carried out to provide a comprehensive overview as well as to highlight the recent contributions related to the environmental evaluation of high-rise and low-rise buildings. The study was carried out by searching the databases of the Scopus and Elsevier in conjunction with ScienceDirect and Google Scholar databases. The reason for this was to cover the published papers in this field up to the highest degree of accuracy. By means of the search of publications quoting the use of LCA in construction sector for the period from 1997 to 2018, more than 230 peer-reviewed publications referencing the use of life cycle assessment in buildings have been identified. The review shows that low-rise buildings (1 similar to 5 floors) compared to high-rise ones (>= 5 floors) received significant attention as the studies focusing on the life cycle assessment of low-rise buildings were about twice in number more than the studies related to the life cycle assessment of high-rise buildings. In case of high-rise buildings, commercial buildings gained more attention by over 60% of the reviewed studies, while for low-rise buildings, residential buildings took the leverage by accounting to over 70% of the reviewed studies. The more frequently studied life cycle stages were those related to the manufacturing and use phases. Similarly, the most considered impact categories were the global warming potential and embodied energy. The reported values for embodied energy of high-rise buildings had a great variation ranging from 0.533 MJ/m(2) to 883.1 GJ/m(2), while the same values for low-rise buildings ranged from 0.21 to 374.4 GJ/m(2). In terms of global warming potential, high-rise buildings emitted 10 to 10,010 kg CO2-eq/m(2) per year, however, some studies revealed the potential of timber structure in emission reduction by values ranging from 234.8 to 1338 kg CO2-eq/m(2). The emissions associated by low-rise buildings ranged from 0.07 to 35,765 kg CO2-eq/m(2), and the respective values for emission reduction by timber structures were between 12.9 and 361 kg CO2-eq/m(2). The results also indicate that a wide range of building's lifespan varying from 20 to over 100 years were utilized in life cycle assessment of different types of buildings. Functional unit was also another parameter that showed a broad variation both in terms of unit and definition. While the majority of researchers considered m(2) as the functional unit (61%), whole building was also considered as the functional unit in almost 20% of the reviewed studies, indicating the lack of standardized definition for functional unit for more practical outcomes. Ecoinvent was the most referred inventory database (65%) for life cycle assessment of buildings followed by University of Bath ICE (11%), U.S. database (9%), and Australian material inventory database (7%). SimaPro dominated computer-aided softwares with 40% of citations among the reviewed studies. ATHENA Impact Estimator and GaBi software gathered the attention of the reviewed studies by 7.5% and 4%, respectively. The review finally highlights that the variations in building design (structure and materials), lifetime, functional unit, and scope restrict to compare the findings and results of studies with each other. (C) 2020 Published by Elsevier B.V.
Keywords: Life cycle assessment; Building sector; Embodied energy; Construction process; Life cycle inventory; GREENHOUSE-GAS EMISSIONS; ZERO-ENERGY BUILDINGS; URBAN RESIDENTIAL BUILDINGS; SINGLE-FAMILY RESIDENCE; OPERATIONAL ENERGY; ASSESSMENT LCA; ENVIRONMENTAL PERFORMANCE; CARBON EMISSIONS; SUSTAINABILITY ASSESSMENT; Construction & Building Technology; Energy & Fuels; Engineering